FITOREMEDIASI PHOSPAT DENGAN PEMANFAATAN ENCENG GONDOK (EICHHORNIA CRASSIPES) (STUDI KASUS PADA LIMBAH CAIR INDUSTRI KECIL LAUNDRY) - Hardyanti, Nurandani; Rahayu, Suparni Setyowati (Universitas Diponegoro, 2007)
Small laundry was one of home industries that grown rapidly. Small laundry industries usually disposed their wastewater straightly to the city drain system without any treatment before. It caused a large amount of phosphate accumulating in the sewage. Because of the environment was unable to handle it by themselves, we needed a simple, cheap, and applicative way to reduce phosphate. Phytoremediation was one of methods to remove phosphate. This research used water hyacinth. Phytoremediation was be done by planting water hyacinth in the phosphate wastewater. By doing this we expected that water hyacinth would absorb the phosphate from the water. The experiments was taken for 5 days with phosphate concentrations of 200 mg/liters; 250 mg/liters; 300mg/liters. At early concentrations of 200mg/l showed that water hyacinth could reduce phosphate until 24.03% or about 144,1603 mg, for the early concentrations of 250 mg/l showed that water hyacinth could reduce 22.95% or about 172.1209 mg and for the early concentrations of 300 mg/liters showed that water hyacinth could absorb about 20,87 % or around 187.860 mg. From the statistic test showed that life time in the wastewater gave a significant result to the ability in absorbing phosphate by the water hyacinth.